The growth of islamic finance in Malaysia : The influential factors / Fatimah Zahra’ Mohd Hanafi - Mohd Hanafi, Fatimah Zahra’ (2011)
This research was conducted to study the factors that influence the growth of Islamic Finance in Malaysia. This study also was conducted to examine the most factors that related to the Islamic finance growth in Malaysia. The researcher had distributed the questionnaires among 70 respondents in MIFC and INCEIF randomly. After collecting the data and analyze, the result shows that there is no association or relationship between financial liberalization and growth of Islamic Finance in Malaysia. The finding also illustrates risk management as the most factors that contribute to growth of Islamic Finance in Malaysia, followed by products innovation. In addition, this study proposed some valuable information that is useful to future researcher to realize and understand the factors that influence the growth of Islamic Finance in Malaysia. Finally, as recommendations, it will assist the responsibility of organizations in order to build on the inherent strengths of Islamic Finance and continue to strengthen the supporting structures. It also to ensure that Islamic Finance will contribute to the overall stability of the global financial system. Keyword : Islamic finance, growth, financial liberalization, products innovation, risk management